2014
DOI: 10.1002/jnr.23459
|View full text |Cite
|
Sign up to set email alerts
|

Mutant disrupted‐in‐schizophrenia 1 in astrocytes: Focus on glutamate metabolism

Abstract: Disrupted-In-Schizophrenia 1 (DISC1) is a genetic risk factor that has been implicated in major mental disorders. DISC1 binds to and stabilizes serine racemase (SR) to regulate production of D-serine by astrocytes, contributing to glutamate (GLU) neurotransmission. However, the possible involvement of astrocytic DISC1 in synthesis, metabolism, re-uptake or secretion of GLU remains unexplored. Thus, we studied the effects of dominant-negative mutant DISC1 on various aspects of GLU metabolism using primary astro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 52 publications
(69 reference statements)
2
10
0
Order By: Relevance
“…1 and Table 1). As mutant DISC1 decreases D-serine production by astrocytes (Ma et al 2013;Abazyan et al 2014), we evaluated whether adding D-serine to cultured neurons would ameliorate deficient dendritic arborization. D-serine treatment significantly restored reduced dendritic length, cell volume, cell area, and had borderline effects on number of dendritic branches and segments in neurons co-cultured with mutant DISC1 astrocytes.…”
Section: Resultsmentioning
confidence: 99%
“…1 and Table 1). As mutant DISC1 decreases D-serine production by astrocytes (Ma et al 2013;Abazyan et al 2014), we evaluated whether adding D-serine to cultured neurons would ameliorate deficient dendritic arborization. D-serine treatment significantly restored reduced dendritic length, cell volume, cell area, and had borderline effects on number of dendritic branches and segments in neurons co-cultured with mutant DISC1 astrocytes.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, genetic variants of DISC1 were shown to be associated with the hippocampal volume [28], cortical thickness [29], and prefrontal-associated cognition [25]. DISC1 protein is predominantly localized in neurons ( [30] and many others), but there is also evidence for a wide extra-neuronal expression (i.e., in cultured astrocytes, OLs, microglia, and radial progenitor cells, [1,23,[31][32][33]). The recently discovered abundant expression of DISC1 in human and rodent OLs [1,23,[33][34][35], together with the well-established influence of DISC1 on white matter integrity [36][37][38], raises the issue, whether OL-associated DISC1 might be part of the aforementioned profound white matter abnormalities in schizophrenia.…”
Section: Introductionmentioning
confidence: 98%
“…We found that expression of C terminus-truncated DISC1 (mutant DISC1), a putative product of chromosomal translocation in a Scottish pedigree [7], disrupts this binding property in a dominant-negative manner, resulting in increased degradation of serine racemase via ubiquitination and decreased production of D -serine [5]. Notably, these changes were observed in astrocytes but not in neurons that expressed mutant DISC1 [5,8], suggesting that mutant DISC1 may exert cell type-specific effects.…”
Section: Introductionmentioning
confidence: 99%